Conceptual crime offender selfinterested identity problem - Atakhanova G.M.; Куаndакоvа М.Zh. (Хабаршы. Заң сериясы, 2017)
This article describes the General characteristics of the personality of the offender and corrupt the structure of the personality of the perpetrator: value orientations and aspirations of the individual, their social position and relationships, interests, needs and habits. Special and deserves our attention the problem of criminal professionalism in selfish crime. Our studies allow you to learn that a large proportion of attacks on other people’s property committed by criminalsprofessionals, and some species, such as pickpocketing, fraud almost completely professionally criminalized. We proposed a model professional selfish crime. identified its main parameters including, for the first time in the National Criminology, selected, described and proven criminal labour market phenomenon as objectively existing phenomenon.